Influence of graphite and aarbon nanotubes on the mechanical and electrical properties of cast epoxy composites - Souza, Clarissa F. M. de (2013)
This study evaluates the influence of graphite and multi-wall carbon nanotubes on the mechanical and electric properties of cast epoxy resin. The epoxy resin based composites were prepared with various graphite and MWNCT content up to 5.0%. Specimens were characterized by DMA, SEM and electric resistivity tests. The observation of fracture surfaces showed a reasonable dispersion of graphite and MWCNT into the epoxy matrix. The graphite and MWCNT have almost the same effect in the electric conductivity of the epoxy composites at low content (0.2 and 0.5 %). The MWCNT composites seem to reach percolation at concentrations near 0.5 % whereas graphite composites reach it at 2%. Higher concentration of graphite and MWCNT have limited effect in the electric conductivity but reduces mechanical properties.